2010
DOI: 10.1590/s1984-46702010000600016
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of epiphytic hydroids (Cnidaria: Hydrozoa) associated to a subtropical Sargassum cymosum (Phaeophyta: Fucales) bed

Abstract: ABSTRACT. Hydroids are broadly reported in epiphytic associations from different localities showing marked seasonal cycles. Studies have shown that the factors behind these seasonal differences in hydroid richness and abundance may vary significantly according to the area of study. Seasonal differences in epiphytic hydroid cover and richness were evaluated in a Sargassum cymosum C. Agardh bed from Lázaro beach, at Ubatuba, Brazil. Significant seasonal differences were found in total hydroid cover, but not in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…All the known hydrozoan species from the peaks of the Gorringe were uniquely collected during summer, thus sampling in other seasons may reveal further hydrozoan diversity due to seasonal patterns of growth of algae and hydroids (e.g. Llobet et al 1991;Fraschetti et al 2002;Montañés et al 2006;Cunha & Jacobucci 2010). Despite that many unreported species are still to be found in the Gorringe at other depths and seasons, the present study already revealed a relatively high species richness of hydroids in a small depth range from the summits of the Gorringe Bank seamounts.…”
Section: Discussionmentioning
confidence: 49%
“…All the known hydrozoan species from the peaks of the Gorringe were uniquely collected during summer, thus sampling in other seasons may reveal further hydrozoan diversity due to seasonal patterns of growth of algae and hydroids (e.g. Llobet et al 1991;Fraschetti et al 2002;Montañés et al 2006;Cunha & Jacobucci 2010). Despite that many unreported species are still to be found in the Gorringe at other depths and seasons, the present study already revealed a relatively high species richness of hydroids in a small depth range from the summits of the Gorringe Bank seamounts.…”
Section: Discussionmentioning
confidence: 49%
“…Areas 0 to 3, 5, 7 to 9, 14 (Figure 1), and areas 0 to 3, 5 to 9 (Figure 2), correspond to Tropical areas, occupying the 22-30°S coastal zone. The endemic species supporting each one of these areas are characterized by species well distributed at the shallow waters of the Brazilian coast, commonly occurring between the intertidal zone and 300m depth, mainly on rocky shore zones (Tables 1, 2;Vannucci Mendes 1946;Vannucci 1949;Migotto 1996;Grohmann et al, 2003;Cunha & Jacobucci 2010;. Areas 4, 10 to 12, 15 (Figure 1), and areas 4, 10 to 12 (Figure 2), correspond to Subtropical areas, occupying the zone from 34-44°S.…”
Section: Resultsmentioning
confidence: 99%
“…Both hydroid species were recorded from DRE in this study. Cunha and Jacobucci (2010) reported 16 species of hydroids on fronds of the alga Sargassum cymosum C.Agardh, 1820 in subtropical Brazil. Among species in their list, A. latecarinata, D. disticha, and O. dichotoma were also found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since hydroids feed on plankton, they likely play an important role in marine ecosystems (Gili and Hughes 1995). Hydroids are often found growing on other marine organisms, including sponges (Calder 1991b), other hydroids (Tang 1991b), deep-sea corals (Henry 2001), molluscs (Kubota et al 1999), arthropods (Genzano 2002), and macroalgae (Fraschetti et al 2006;Cunha and Jacobucci 2010;Oliveira and Marques 2007). Except for the well-known association between proboscidactylid polyps and sabellid polychaetes (Schuchert 2009), relatively, little attention has been given to worm tubes as substrates for hydroids.…”
Section: Introductionmentioning
confidence: 99%